Character Cultivation Through Ro'an (Gotong Royong) Tradition in Walisongo Islamic Boarding School (International Journal of Education and Literature, 2025)
This study aims to determine the efforts to develop character through ro'an (mutual cooperation) actions at the Walisongo Sukajadi Islamic Boarding School. The problem is that in the Islamic boarding school there is a ro'an tradition, namely the tradition of mutual cooperation of students in carrying out the mandate of the boarding school caretaker. The Wali Songo Islamic Boarding School is one of the salafiyyah boarding schools in Central Lampung which has two ro'an traditions, namely monthly or grand ro'an and daily ro'an. Daily ro'an is a ro'an that is specifically carried out by students nderek ndalem or nderek kyai. Through this tradition, the boarding school caretaker tries to instill a character of responsibility and honesty in students. This study is a qualitative study where the researcher provides descriptive data in the form of words, pictures, and not values. Data were obtained from observation, interviews, and documentation. The results of the study showed (1) The implementation of ro'an activities at the Wali Songo Islamic Boarding School went well. The implementation of ro'an is divided into two activities, namely ro'an carried out by some students and ro'an carried out by all students. Daily ro'an is carried out by the nderek students and is carried out by coordinating between students so that all work entrusted can be completed properly; (2) Instilling a character of responsibility in students through ro'an, including by giving mandates, giving direction, input, and motivation. Meanwhile, instilling an honest character includes getting students used to being honest in everything they do, and giving students trust; (3) The results of ro'an activities in instilling a character of responsibility make students more responsible in carrying out everything they do. Meanwhile, the impact of ro'an activities in instilling an honest character is that students are used to being honest in everything they do.